1997
DOI: 10.1017/s0021859697004760
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of animal output and nitrogen leaching losses recorded from drained fertilized grass and grass/clover pasture

Abstract: Annual liveweight gain of beef cattle (steers) grazing grass pasture fertilized with 200 kg N\ha was compared over a period of 7 years with that of steers grazing grass\white clover pasture given no artificial N fertilizer at North Wyke, Devon, UK. Nitrogen lost by leaching over the ensuing winter drainage periods was monitored from both pastures. Nitrogen leaching loss from the fertilized pasture over an extended period of 13 years (1983-95) is also reported.The average annual liveweight gain of the steers g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 0 publications
5
38
0
Order By: Relevance
“…Surface water flowed from the drained plots on 21 days during the year. In 1994 there was more rain and drainage than usual: the 30‐year mean rainfall (1966–95) is 1055 mm, with 480 mm excess drainage, occurring over 139 days (Tyson et al . 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Surface water flowed from the drained plots on 21 days during the year. In 1994 there was more rain and drainage than usual: the 30‐year mean rainfall (1966–95) is 1055 mm, with 480 mm excess drainage, occurring over 139 days (Tyson et al . 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it is now generally believed that the smaller N losses with grass‐clover swards are due to the lower level of livestock production and that the two systems (grass‐clover swards receiving no N fertilizer and N‐fertilized grass swards) would release similar amounts of nitrate at equal levels of livestock production per hectare (Cuttle et al. , 1992; Tyson et al. , 1997; Hooda et al.…”
Section: The Potential Of Legumes To Reduce Air and Water Pollutionmentioning
confidence: 99%
“…Soil moisture stress has also been linked with NO3 -leaching. Tyson et al (1997) found that NO3 -leaching over a 13-year period from the fertilized grassland was significantly correlated with the preceding summer's soil moisture deficit (SMD), with the highest losses after dry summers. Soil moisture stress can contribute to increased NO3 -leaching through reducing crop uptake and/or organic N released from the soil microbial biomass during soil rewetting (Halverson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%